Fractal Analyses of HRV Signals: A Comparative Study - Akay, M.; Fischer, R. (Methods of Information in Medicine, 1997)
In this paper, we have investigated the scaling behavior of the heart rate variability signals using the power spectral density (PSD), the discrete wavelet transform (DWT), and dispersive analysis (DA), and the maximum likelihood estimator (MLE) method. Results suggested the lowest variance for the MLE method, greatest variance for the PSD methods, the other methods somewhere in between.
Keywords: Fractal; Fractional Brownian Motion; Wavelets